Forward thinking: correlates of posttreatment outcome expectation among depressed outpatients / Pensamiento prospectivo: correlatos de las expectativas de resultados post-tratamiento de pacientes ambulatorios que sufren depresión. Issue 2 (1st September 2016) - Constantino, Michael J.; Vîslă, Andreea; Ogrodniczuk, John S.; Coyne, Alice E.; Söchting, Ingrid
Abstract: Although patients' expectation about a treatment's efficacy correlate with beneficial therapy processes and outcomes, scant research addresses patients' expectation for lasting improvement at treatment's end. Given the influence of beliefs on psychological functioning, posttreatment outcome expectation reflects an important acute treatment outcome. In this study, we examined patient characteristics, treatment processes and clinical change factors in relation to the posttreatment outcome expectation of 65 depressed outpatients completing group cognitive-behavioural therapy. Less than 1% of variability in posttreatment outcome expectation was due to group effects; thus, we conducted single-level regressions. Patients with less severe baseline depression, higher session 3 outcome expectation, more during-treatment hope and a greater reduction in interpersonal problems reported greater posttreatment outcome expectancy. Various patient characteristics and change factors can help clinicians forecast, and respond to, those patients who will possess stronger or weaker belief in their ability to maintain therapy gains at treatment's end.